1970
DOI: 10.1021/ja00709a070
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small-ring heterocyclic compounds. XXIV. Photoisomerization of the triphenyl-1,3-diazabicyclo[3.1.0]hex-3-ene system

Abstract: 5 ) All the calculations used an average C plus S f-curve for the two disordered ring atoms.(6) The crystal structure of histidine was refined by J. Donohue and A. Caron, Acta Crystallogr., 17, 1178 (1964), but the conformation about the C-C bond is given in ref 3.(7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…9 Coupling constants and NOE measurements (irradiation of HC-2 gives rise only to enhancement of HC-6) provided exhaustive information on the exo-stereochemistry of the process.…”
Section: Methodsmentioning
confidence: 99%
“…9 Coupling constants and NOE measurements (irradiation of HC-2 gives rise only to enhancement of HC-6) provided exhaustive information on the exo-stereochemistry of the process.…”
Section: Methodsmentioning
confidence: 99%
“…In solution, the lifetime of the colored intermediates was much shorter (several minutes at room temperature) and their formation was not entirely reversible due to a competing enediimine formation (12,23). In an earlier report (12), we had shown that the enediimine was formed via transient colored intermediates which were 1,3-dipoles (azomethine ylides).…”
Section: Photochromism In Mono-cyclic Aziridinesmentioning
confidence: 98%
“…Typical of the compounds which were investigated (Table II) In solution, the lifetime of the colored intermediates was much shorter (several minutes at room temperature) and their formation was not entirely reversible due to a competing enediimine formation (12,23). In an earlier report (12), we had shown that the enediinine was formed via transient colored intermediates which were 1,3-dipoles (azomethine ylides).…”
Section: Photochromism In Bicyclic Aziridinesmentioning
confidence: 99%